2018
DOI: 10.1002/qre.2364
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of social network anomaly detection using a moving window–based scan method

Abstract: Timely detection of anomalous events in networks, particularly social networks, is a problem of increasing interest and relevance. A variety of methods have been proposed for monitoring such networks, including the window‐based scan method proposed by a previous study. However, research assessing the performance of this and other methods has been sparse. In this article, we use simulated social network structures to study the performance of the Priebe et al method. The detection power is high only when more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Jones‐Farmer et al discussed the importance of effectively collecting and analyzing baseline data during Phase I. If the network being monitored is expected to evolve over time, then we recommend moving window approaches as opposed to a fixed Phase I sample as considered in other studies …”
Section: The Network Surveillance Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones‐Farmer et al discussed the importance of effectively collecting and analyzing baseline data during Phase I. If the network being monitored is expected to evolve over time, then we recommend moving window approaches as opposed to a fixed Phase I sample as considered in other studies …”
Section: The Network Surveillance Problemmentioning
confidence: 99%
“…Perry developed an EWMA control chart to monitor the hierarchy present in directed networks. Both Zhao et al and Noorossana analyzed the use of control charts for dynamic anomaly detection in social networks.…”
Section: Related Workmentioning
confidence: 99%
“…Zhao et al [25] have shown that 4, rather than the value 5 recommended by Priebe et al [24], is a reasonable signaling threshold. Thus, a signal indicating the possible presence of an anomaly is generated at time t if .…”
Section: Network Model and Surveillance Methodsmentioning
confidence: 99%
“…Woodall et al [4], Savage et al [5], Zhao et al [25] and Fricker [26] all argued that the use of synthetic data is necessary when studying network monitoring methods. We agree with this argument because the temporal information of network anomalies within any existing set of network data can be difficult to determine at best.…”
Section: Description Of Simulationmentioning
confidence: 99%
“…Woodall et al provided an overview of social networking monitoring and discussed relationships with other types of monitoring. Zhao et al studied the properties of the scan method of Priebe et al under the assumption of the Erdős and Rényi model. In addition, we have studied monitoring under the assumption of the degree‐corrected stochastic block model (see the works of Wilson et al, Zhao et al, and Yu et al).…”
Section: Social Network Surveillancementioning
confidence: 99%